1993
DOI: 10.1021/bi00092a012
|View full text |Cite
|
Sign up to set email alerts
|

Chemical probing of tDNAPhe with transition metal complexes: A structural comparison of RNA and DNA

Abstract: The three-dimensional folding of tDNAPhe has been examined and compared to native tRNAPhe using a series of shape-selective transition metal complexes as chemical probes of nucleic acid structure. Rh(phen)2 phi 3+ (phen = phenanthroline, phi = 9,10-phenanthrenequinonediimine), which targets sites of tertiary interaction in tRNAPhe, cleaves specifically at similar sites on tDNAPhe. However, this rhodium complex also targets 5'-pyr-pyr-pur-3' sites within the acceptor and anticodon stems of tDNA;Rh(phen)2 phi 3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…One role of the 2Ј-hydroxyls (in tRNA at least) is to increase the stability of the molecule (12). Studies using transition metal complexes have confirmed that the global structure of tDNA Phe resembles that of tRNA Phe but that the base paired stem conformations differ somewhat (13 (14). All of the above studies were conducted using canonical base replacements (A, C, G, T, and deoxyribose for the tDNA analogues) and demonstrate that tDNA and tRNA can have similar conformations in solution.…”
Section: Resultsmentioning
confidence: 99%
“…One role of the 2Ј-hydroxyls (in tRNA at least) is to increase the stability of the molecule (12). Studies using transition metal complexes have confirmed that the global structure of tDNA Phe resembles that of tRNA Phe but that the base paired stem conformations differ somewhat (13 (14). All of the above studies were conducted using canonical base replacements (A, C, G, T, and deoxyribose for the tDNA analogues) and demonstrate that tDNA and tRNA can have similar conformations in solution.…”
Section: Resultsmentioning
confidence: 99%
“…If the metal is redox active at physiological conditions, as it is for copper, radical cleavage should occur at the MC/RNA binding site to report on the RNA shape. In solution, Cu-phen binds at RNA loops, bulges, and helix distortions in tRNA, mRNA, and rRNA that are indistinguishable for most alkylating agents and too small for access by protein nucleases (3)(4)(5)(6)(7). We now show that Cu-phen, an MC, detects the tertiary structure in ferritin mRNA in HeLa cells selectively distinguishing the wild type IL/B from a mutant IRE.…”
mentioning
confidence: 82%
“…Do mRNA tertiary structures such as the ferritin mRNA IRE form in vivo? Metal coordination complexes (MCs), protein nucleases, and alkylating agents have all been used to analyze mRNA solution structure, but MCs are particularly sensitive to the tertiary structure or shape of the RNA binding site (3)(4)(5)(6)(7). MCs have specific geometry and relatively rigid shapes contributed by small organic molecules, coordinated to a metal ion (Fig.…”
mentioning
confidence: 99%
“…For DNA, however, the database of secondary structures determined by physical means or by comparative sequence analysis is much smaller (7,10,11,14,19,27,30,31,35,43,61,78). Table 5 shows the secondary structure prediction results for the currently available DNA database.…”
Section: Quality Of Secondary Structure Predictionsmentioning
confidence: 99%